2010
DOI: 10.1002/hep.23600
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Peripheral Cholangiocarcinoma in Cirrhosis Patients May Display A Vascular Pattern Similar to Hepatocellular Carcinoma on Contrast-Enhanced Ultrasound

Abstract: The aim of this study was to describe the imaging features by contrast-enhanced ultrasound (CEUS) of intrahepatic cholangiocarcinoma (ICC) in cirrhosis patients. We registered the CEUS images of cirrhosis patients with histologically confirmed ICC. In all cases magnetic resonance imaging (MRI) was done to confirm the diagnosis and/or staging purposes. A total of 21 patients met all the criteria to be included in the study. The median nodule size was 32 mm. All nodules showed contrast enhancement at arterial ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
236
7
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(253 citation statements)
references
References 31 publications
9
236
7
1
Order By: Relevance
“…These were peripheral irregular rim-like hyperenhancement, heterogeneous hyperenhancement, homogeneous hyperenhancement and heterogeneous hypo-enhancement [10,[14][15][16][17]. In the present study, the most common type of ICC was the mass-forming type (80%).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…These were peripheral irregular rim-like hyperenhancement, heterogeneous hyperenhancement, homogeneous hyperenhancement and heterogeneous hypo-enhancement [10,[14][15][16][17]. In the present study, the most common type of ICC was the mass-forming type (80%).…”
Section: Discussionsupporting
confidence: 46%
“…In addition, different morphological subtypes tended to exhibit distinct enhancement characteristics on CT [7,8,[11][12][13]. On CEUS, besides the specific feature of peripheral rim-like hyperenhancement, diverse imaging findings of ICC were reported [9,10,[14][15][16][17]. These different CEUS appearances may reflect the differences in pathological subtypes or components of ICC.…”
mentioning
confidence: 97%
“…Intrahepatic cholangiocarcinoma (ICC) is a tough diagnostic challenge duo to its asymptomatic clinical features and atypical imaging characteristics [17,18]. Commonly, it is more difficult to distinguish smaller ICC (diameter ≤3 cm) from HCC on CEUS, corresponding to more frequently appeared homogeneous hyperenhancement [19]. In our study, similar with the entire clips, the 0-1min clips could correct diagnose 14 in 16 patients.…”
Section: Discussionmentioning
confidence: 61%
“…However, a few years later, Vilana et al reported that intrahepatic cholangiocellular carcinoma (ICC) in cirrhotic liver may not be clearly distinguishable from HCC at CEUS [20]. A total of 21 patients were evaluated.…”
mentioning
confidence: 99%
“…As reported by D'Onofrio et al, the behavior of ICC at CEUS is different from the one in CT. During the late phase, ICC appears hypervascular at CT, because of desmoplastic reaction due to fibrotic component, while at CEUS it appears hypovascular [22]. In these cases CEUS should not be used as the sole imaging technique for conclusive hepatocellular carcinoma diagnosis and if the MRI does not display the diagnostic vascular pattern, a confirmatory biopsy is mandatory [20]. More recently, de Sio et al enrolled 282 cirrhotic patients who underwent CEUS and subsequent biopsy with histological evaluation as the gold standard for correct classification of FLLs.…”
mentioning
confidence: 99%